Understanding digital remittance adoption: The role of credibility, ease of use, and promotion with technological anxiety as a moderator in Indonesia - Genesis Sembiring Depari; Steven; Jen Peng Huang (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study examines the influence of credibility, perceived ease of use, and promotion on users' behavioral intention in using digital remittance services in Indonesia, with a focus on the moderating role of technological anxiety. It aims to understand how these factors shape user engagement and whether technological anxiety alters these relationships. A structured survey was conducted among Top Remit users to collect data on their perceptions and experiences. Findings indicate that credibility, ease of use, and promotion have a positive influence on behavioral intention, highlighting the importance of trust, platform simplicity, and effective marketing. While technological anxiety directly affects behavioral intention, it does not significantly moderate the relationships between credibility, ease of use, and promotion. Enhancing credibility, user experience, and balanced promotions fosters user adoption. The study offers practical insights for digital service providers to enhance user satisfaction and overcome technological barriers.